G6PD Variants and Haemolytic Sensitivity to Primaquine and Other Drugs - Bancone, Germana; Chu, Cindy S. (Frontiers in Pharmacology, 2021)
Restrictions on the cultivation and ingestion of fava beans were first reported as early as the fifth century BC. Not until the late 19th century were clinical descriptions of fava-induced disease reported and soon after characterised as “favism” in the early 20th century. It is now well known that favism as well as drug-induced haemolysis is caused by a deficiency of the glucose-6-phosphate dehydrogenase (G6PD) enzyme, one of the most common enzyme deficiency in humans. Interest about the interaction between G6PD deficiency and therapeutics has increased recently because mass treatment with oxidative 8-aminoquinolines is necessary for malaria elimination. Historically, assessments of haemolytic risk have focused on the clinical outcomes (e.g., haemolysis) associated with either a simplified phenotypic G6PD characterisation (deficient or normal) or an ill-fitting classification of G6PD genetic variants. It is increasingly apparent that detailed knowledge of both aspects is required for a complete understanding of haemolytic risk. While more attention has been devoted recently to better phenotypic characterisation of G6PD activity (including the development of new point-of care tests), the classification of G6PD variants should be revised to be clinically useful in malaria eliminating countries and in populations with prevalent G6PD deficiency. The scope of this work is to summarize available literature on drug-induced haemolysis among individuals with different G6PD variants and to highlight knowledge gaps that could be filled with further clinical and laboratory research.